Front desk customer service for queue management system - Mohamad Fazli, Alias (2007)
Front desk customer service for queue management system is a system that help the customer to manage their business when they at the place that provide the customer service. There are many applications that have been develop base on the service provided by this system in electronic field nowadays such as thermal printer, LCD Touch Screen, push button panel option, high speed system structure without needing and external computer, special display and console design, monitoring system, moving message, and TV units can be adapted to the system, multiple ticket machine supported, WAN, LAN, internet supporting through TCP/IP and according to the customer needs, additional function are supported. The purpose of this project is to develop a Queue Management System model that can display a number display module, a queue module and a sound module. The system was controlled by PIC Microcontroller as a system controller. By using PIC 16F877, push button, decoder, latch, LED, seven segment, buzzer and voltage regulator circuit, the operational of this system were programmed using the PIC Basic programming language. As the result, the Queue Management System is operated as the expected operation and be able to achieve the objective of the project.